2002
DOI: 10.1177/070674370204700804
|View full text |Cite
|
Sign up to set email alerts
|

Effective Use of Electroconvulsive Therapy in Late-Life Depression

Abstract: Objective: To review literature pertaining to the efficacy, safety, and tolerability of electroconvulsive therapy (ECT) in treating late-life depression. Method:We undertook a literature review with an emphasis on research studies published in the last 10 years.Results: There is a positive association between advancing age and ECT efficacy. Age per se does not necessarily increase the risk of cognitive side effects from ECT, but this risk is increased by age-associated neurological conditions such as Alzheimer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
4

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 57 publications
1
28
0
4
Order By: Relevance
“…To our knowledge, this is the first time that treatment with index ECT of a geriatric patient group with medication-resistant depression shows cognitive improvement that lasts for at least 1 year [Flint and Gagnon, 2002;Tew et al, 1999;Wesson et al, 1997;Wilkinson et al, 1993;Zervas et al, 1993]. The results, although based on a relatively small number of subjects, thus indicate that older people given ECT for severe mood disorder do not suffer cognitive decline at long-term follow-up, but even show a benefit of ECT treatment.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…To our knowledge, this is the first time that treatment with index ECT of a geriatric patient group with medication-resistant depression shows cognitive improvement that lasts for at least 1 year [Flint and Gagnon, 2002;Tew et al, 1999;Wesson et al, 1997;Wilkinson et al, 1993;Zervas et al, 1993]. The results, although based on a relatively small number of subjects, thus indicate that older people given ECT for severe mood disorder do not suffer cognitive decline at long-term follow-up, but even show a benefit of ECT treatment.…”
Section: Discussionmentioning
confidence: 80%
“…The more recent study of Brodaty et al [2000] did include cognitive measures but did not provide details of ECT-techniques used. In a review, Flint and Gagnon [2002] concluded that ECT can be used safely in patients of very advanced age, with appropriate evaluation and monitoring, and administration in an optimal way. They suggest that the superior response to ECT among older compared with younger adults might not be related to aging per se but to age-related clinical factors, such as lengthier depressive episodes and more melancholic features in their mood.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In some reports, authors make references to situations in which there is an increasing risk with 5 the procedure, [40][41][42][43] such as intracranial lesions or conditions associated to an increase in the intracranial pressure, 40,43 history of cerebrovascular accident, 41,42 recent myocardial infarction with cardiac decompensation, severe systemic arterial hypertension (especially if it is associated with pheochromocytoma), presence of risk factors for intracranial hemorrhage and any condition associated to a 4 or 5 risk score of the American Society of Anestheologists (ASA). 18,44 It is also not contraindicated during pregnancy.…”
Section: Contraindicationsmentioning
confidence: 99%